High‐Fat Diet Induces Leptin Resistance in Leptin‐Deficient Mice. (February 2014) - Koch, C. E.; Lowe, C.; Pretz, D.; Steger, J.; Williams, L. M.; Tups, A.
<x xml:space="preserve">Abstract</x> The occurrence of type II diabetes is highly correlated with obesity, although the mechanisms linking the two conditions are incompletely understood. Leptin is a potent insulin sensitiser and, in leptin‐deficient, insulin insensitive, Lepob/ob mice, leptin improves glucose tolerance, indicating that leptin resistance may link obesity to insulin insensitivity. Leptin resistance occurs in response to a high‐fat diet (HFD) and both hyperleptinaemia and inflammation have been proposed as causative mechanisms. Scrutinising the role of hyperleptinaemia in this process, central hyperleptinaemia in Lepob/ob mice was induced by chronic i.c.v. infusion of leptin (4.2 μg/day) over 10 days. This treatment led to a dramatic decline in body weight and food intake, as well as an improvement in glucose tolerance. Transfer to HFD for 4 days markedly arrested the beneficial effects of leptin on these parameters. Because Lepob/ob mice are exquisitely sensitive to leptin, the possibility that leptin could reverse HFD‐induced glucose intolerance in these animals was investigated. HFD led to increased body weight and glucose intolerance compared to a low‐fat diet (LFD). Older and heavier Lepob/ob mice were used as body weight‐matched controls. Mice in each group received either i.p. leptin (1.25 mg/kg) or vehicle, and glucose tolerance, food intake and the number of phosphorylated signal transducer and activator of transcription (pSTAT)3 immunoreactive cells in the arcuate nucleus (ARC) and ventromedial hypothalamus (VMH) were analysed. Leptin improved glucose tolerance (P = 0. 019) and reduced food intake in Lepob/ob mice on LFD (P ≤ 0.001) but was ineffective in mice on HFD. Furthermore, when leptin was administered centrally, the glucose tolerance of Lepob/ob mice on HFD was significantly impaired (P = 0.007). Although leptin induced the number of pSTAT3 immunoreactive cells in the ARC and VMH of Lepob/ob mice on LFD, HFD was associated with elevated pSTAT3 immunoreactivity in vehicle‐treated Lepob/ob mice that was unaffected by leptin treatment, suggesting central leptin resistance. Negating central inflammation by co‐administering a c‐Jun n‐terminal kinase (JNK) inhibitor reinstated the glucose‐lowering effects of leptin. These findings demonstrate that Lepob/ob mice develop leptin resistance on a HFD independent of hyperleptinaemia and also indicate that the JNK inflammatory pathway plays a key role in the induction of diet‐induced glucose intolerance.